Perceptions of Manager's Regarding the Role of Educational Factors in Creativity and Job Innovations of Entrepreneurship and Successiveness of Agricultural Cooperatives - zahra goodarzi; bahman khosravi pour; masoud baradaran; mansour ghanian; nozar monfared (تعاون و کشاورزی, 2016)
The role of education in promoting culture of entrepreneurship in agricultural sectors is important.  The purpose of this survey was to identify educational factors influencing entrepreneurship of agricultural cooperatives, evaluation of creativity and job innovation and entrepreneurial spirit of Khuzestan cooperatives managers (Ahvaz and Dezful). The population consisted of 100 agricultural cooperatives and Samples were 80 agricultural cooperatives in Khuzestan with using Krejcie and Morgan Table. Then 2 managers and board of directors for each cooperative (totally 160) were selected. Data collected by a questionnaire and personal interview. For analyzing data SPSS (16) was used. Validity of the questionnaires has been confirmed by faculty members and experts. Its reliability confirmed by using of pilot test in Ahvaz rural cooperatives. Cronbach's Alpha value was reported for technical and educational factors as 0.85 percent. Result indicated that education level of members and Implementation of educational courses with entrepreneurship target, rate of creativity and job innovation and entrepreneur spirit were important in cooperative’s success. Technical skills of manager, educational level, board of director’s professional and technical skills had most importance respectively.